O direito fundamental à publicidade dos atos normativos e a comunicação pública estatal: um estudo de caso sobre os decretos de quarentena (COVID-19) em municípios do Estado de Minas Gerais - Ana Beatriz Rezende Rosa (2023)
The COVID-19 pandemic has changed social dynamics in the public and private spheres. Considering the initial absence of the vaccine, it was necessary to adopt quarantine measures in order to restrict people's face-to-face contact and reduce the spread of viruses. Such acts were usually established by municipal executive branch’s norms, especially by decrees. In this scenario, this research aimed to understand, from the analysis of the publicity given to the quarantine decrees edited due to the policy to face COVID-19 on Facebook and Instagram profiles of the City Halls of the most populous and less populous cities of the Intermediate Regions of the State of Minas Gerais, if it was possible to observe the guarantee of the fundamental right to publicity, foreseen in art. 37 of CRFB/88, from the perspective of Formal Legistics and the public communication. In view of this objective, a theoretical and empirical research was carried out, which consisted of collecting data from the official websites, Facebook and Instagram profiles of the City Halls of the above-mentioned groups of cities, based on an observation form. The results pointed to the guarantee of the publicity of normative acts right in different degrees according to the city, with a discrepancy, in general, very large in the publicity promoted by the most populous and less populous cities of each Intermediate Region of the state. The conclusions point to the need to improve the publicity policy of the municipalities, despite the challenges being different according to each municipal reality.